15 years later: Post 9/11 support for increased security and criminalizing muslims. Issue 4 (2nd October 2017) - Aizpurua, Eva; Singer, Alexa J.; Butler, Leah F.; Collier, Nicole L.; Gertz, Marc G.
ABSTRACT: Islamophobia appears to be growing, becoming a mainstream ideology in the United States. Despite the current spike in anti-Islamic sentiment and fear of the Islamic "other, " these ideas are not new and can be traced back to the September 11, 2001, terrorist attacks. Using survey data collected only months after the attacks ( N = 422), this study uses an integrated threat framework to examine predictors of public support for increased security in the United States. The results show that perceived personal threat and support for policies that criminalize Muslims predict support for security policies that compromise civil liberties. This is especially true among older individuals, conservatives, individuals less inclined towards individual freedom, and those living in the Northeast or in the South.